MDM2 Is Essential to Maintain the Homeostasis of Epithelial Cells by Targeting p53 - Su Wang; Shufen Zhong; Ying Huang; Songling Zhu; Shuangfeng Chen; Ran Wang; Sonam Wangmo; Bo Peng; Houkun Lv; Jichao Yang; Liyan Ma; Zhiyang Ling; et al. (Karger Publishers, 2024)
Introduction: MDM2 is known as the primary negative regulator of p53, and MDM2 promotes lung cancer fibrosis and lung injury through p53-dependent and p53-independent pathways. However, the mechanism by which MDM2 influences the pathogenesis of asthma is unknown. In this study, we investigated the function of MDM2 in lung epithelial cells in type 2 lung inflammation. Methods: We used type II alveolar epithelial cell-specific heterozygous knockout of Mdm2 mice to validate its function. Then papain-induced asthma model was established, and changes in inflammation were observed by measuring immunohistochemistry and flow cytometry analysis. Results: In this study, we knockdown the mouse Mdm2 gene in type 2 alveolar epithelial cells. We demonstrated that heterozygous Mdm2 gene-deleted mice were highly susceptible to protease allergen papain-induced pulmonary inflammation characterized by increased ILC2 numbers, IL-5 and IL-13 cytokine levels, and lung pathology. A mechanistic study showed that following the decreased expression of Mdm2 in lung epithelial cells and A549 cell line, p53 was overactivated, and the expression of its downstream genes p21, Puma, and Noxa was elevated, which resulted in apoptosis. After Mdm2 knockdown, the mRNA expression of inflammation-related gene IL-25, HMGB1, and TNF-α were increased, which further amplified the downstream ILC2 response and lung inflammation. Conclusion: These results indicate that Mdm2 maintains the homeostasis of lung epithelial cells by targeting P53 and regulates the function of lung epithelial cells under type 2 lung inflammation.